IMPLEMENTASI PEMERINTAH KOTA BUKITTINGI DALAM KERJASAMA SISTER CITY DENGAN PERBANDARAN SEREMBAN - Ayu Lestari Yulia Fitri; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Autonomous regions and globalization has encouraged an increase in the capacity of the government and the town of Bukittinggi in good governance as a prerequisite for development and a step that makes the fabric of wider cooperation. It encourages the development of sister city cooperation Bukittinggi city government and the Seremban Municipal.Implementation describes the successful cooperation of Bukittinggi and Seremban Municipal. The study used Pluralism perspective. Used theoretical framework cooperation theory, effectiveness, as well as the concept of sister city.In connection with the objectives to be achieved together, the cooperation between the government of Bukittinggi and the Seremban Municipal sister city cooperation greatly helped the city of Bukittinggi in developing all the advantages of natural resources and beauty that can not be in doubt. This study uses primary data that is direct observation of the application of the sister city in Bukittinggi town and using qualitative analysis research. The results showed that the implementation of the implementation of cooperation sister city of Bukittinggi and Seremban Municipal positive impact and can be utilized by the town of Bukittinggi in developing amcam various agreements that have been listed in the agreement between the city and the Municipal Bukitttinggi Seremban.Keywords: Sister City, Cooperation, Bukittinggi and Perbandaran Seremban